Words and meanings lexical semantics across domains, languages, and cultures - Goddard, Cliff; Wierzbicka, Anna (Oxford linguistics., 2014)
"In a series of cross-cultural investigations of word meaning, Cliff Goddard and Anna Wierzbicka examine key expressions from different domains of the lexicon - concrete, abstract, physical, sensory, emotional, and social. They focus on complex and culturally important words in a range of languages that includes English, Russian, Polish, French, Warlpiri and Malay."--Publishers website.